The influence of ethical leadership and ethical culture on ethical behavior in higher education institutions - Anik Herminingsih (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Educational institutions play a crucial role as examples of ethical behavior enforcement in society. This study aims to examine the influence of ethical leadership on ethical behavior through the mediating role of ethical culture in Universitas Mercu Buana, a higher education institution accredited in Jakarta. Specifically, the research investigates how leadership shapes the ethical culture and, subsequently, ethical behavior among academic and administrative staff, thereby setting an example for students in ethical behavior formation. The research employs a quantitative approach with a causality design. Data were collected using structured questionnaires distributed to 150 academic and administrative staff as respondents, selected through purposive sampling. The data were analyzed using the Structural Equation Model (SEM) with the AMOS software to identify direct and indirect relationships between variables. The findings reveal that ethical leadership has a significant positive effect on ethical culture (CR = 4.233, P = 0.000) and ethical behavior (CR = 6.677, P = 0.000). Furthermore, ethical culture mediates the relationship between ethical leadership and ethical behavior, emphasizing its pivotal role in shaping ethical practices. These results highlight the importance of fostering ethical leadership and culture within educational institutions to promote ethical behavior. The study concludes that strengthening ethical leadership and cultivating an ethical culture in higher education can significantly contribute to forming ethical attitudes and behaviors, which are essential for graduates and society. Practical implications include the need for ethics-based leadership training and the establishment of institutional policies that reinforce ethical norms. These findings offer valuable insights for both academic researchers and practitioners in organizational ethics.